편성 규제 정책의 패러다임 전환을 위한 시론적 논의 : 편성 규제 개정 경과와 위반 현황을 중심으로 - 정영주(YoungJu Jung); 황현정(Hyunjung Hwang) (언론정보연구, 2024)
이 연구는 현행 편성 규제의 개정 경과를 통해 정책의 특성을 살펴보고, 방송 사업자들의 편성 규제 위반 현황에서 함의를 도출하여 현행 편성 규제 정책에 변화가 필요하다는 것을 제기하고자 한 것이다. 이를 위해 방송프로그램 분야별 균형 편성, 주된 방송 분야 프로그램 의무 편성, 수중계 편성 비율 제한, 국내 제작 방송프로그램의 편성 비율, 1개 국가 제작물 편성 제한, 순수외주제작 방송프로그램 의무 편성 등 6개 편성 규제 항목의 개정 경과를 살펴보고 2013년 이후 방송 사업자들의 편성 규제 위반 사례를 전수 분석했다. 2000년 방송법 이후 편성 규제는 미디어 환경의 변화에도 규제 항목을 폐지하거나 재검토하지 않고 편성 비율을 조정하거나 산정 주기를 확대하는 방식으로 경로를 형성하며 관행적으로 유지되는 정책의 경로 의존성을 답습해 왔다. 다수의 편성 비율 규제 항목에도 불구하고 방송 사업자들의 위반 사례는 많지 않고 위반 사례가 전혀 없는 항목들도 다수 존재하며 위반 건수가 많은 항목은 대부분 오랫동안 비율 변동 없이 유지된 항목들인 것으로 나타났다. 변화한 미디어 환경을 반영하여 편성 규제가 애초 상정한 정책 목표를 달성하는데 적합한 정책 수단인지에 대한 근본적인 검토가 필요하며, 편성 정책의 전환과 편성 개념의 확장을 통해 편성 규제의 패러다임 전환을 모색해야 할 시점이다. This study examined the characteristics and effectiveness of programming regulations by analyzing their revision history and broadcasting operators’ violations to raise the need for revising current regulations. The study aimed to suggest the future directions for the programming policies. To achieve this, the study analyzed the revision history of six specific programming regulations, including the balanced programming regulations by program genre, mandatory programming in specialized genres, re-broadcasting program quotas for regional broadcasting companies, domestic program quotas, the quotas for programs imported from a single country, the quotas for purely outsourced programs. The study comprehensively analyzed cases of regulation violations by broadcasting operators since 2013. The programming regulations have not been abolished or restructured in detail, but have been kept with minor adjustments, such as adjusting ratios of quotas or the base period of calculation ratios since the Broadcasting Act of 2000. The implementation of programming regulations has been path-dependent despite dynamic changes in media environments. Only a few broadcasting companies have violated the regulations, and many regulations have not had a single violation case. It is noted that regulations with a high number of violations have mostly maintained ratios for a long time without revisions. A comprehensive review of the fundamental policy is necessary to determine whether the regulations are appropriate to achieve the initial objectives. Furthermore, it is suggested that the programming regulations should be explored through the reconceptualization of programming and the programming policies in changing media environments. KCI Citation Count: 0